MEMBANGUN KONSTRUKSI POLITIK HUKUM MEDIASI PENAL SEBAGAI ALTERNATIF PENYELESAIAN PERKARA PIDANA - Umi Rozah (Masalah-Masalah Hukum, 2010)
Build upon this research on "Building Leval Policy Construction on Penal Mediation as Alternative in Criminal Matters Settelement". obtained that practices of penal mediation in society which is popular as "kinship settlement" in certaint criminal cases, such as complaints offences (compalints delict), negligance offences, offences that result with small lost, offences in family relationship, and domestic abused offences. But nowadays, an agreement as result of penal mediation settlement in practices by society does't have binding of law cause of no provision that regulate it. Furthermore, even if an restitution has fulfielled for victim could be prosecuted in criminal justice process cause of his/her offences. Thile in special cases, practices of penal mediation could be performed in all stages in criminal justice process, such as in process og investigation, prosecution, and justice. However, an agreement as result of penal mediation between performance. An agreement just could be used to be one of reasons to consider to make light of punishment. Facts show up that society and law enforcement officer need alternative settlement in criminal institutionalization of penal mediation in special cases. Furthermore its need acknowledment and institutionalization of penal mediation as part of criminal justice process under penal mediation enactment. The needs of penal mediation accordance with penal law reform concept in draft Indonesia Penal Code 2008 (RUU KUHAP) in article 145, that enacted penal mediation (settlement out of court) as one of reasons to come off presecution authority. In this initial research, created legal polity construction in penal mediation, and established of policy in penal mediation performance in future such as juridical definition, offences could be solved by penal mediation, principles of penal mediation, and penal mediation settlement either perform out of criminal justice process or within criminal justice process. This research base on Research Methods with socio legal research-doctrinal approach, specification by descriptive analysis, that need primary and secondary data. Primary data be obtained by interview with Police Departement Officers, Prosecutors, and Judges. Analysis methods use qualitative analysis.Kata Kunci : Membangun, Konstruksi, Politik Hukum, Mediasi penal.